2023
DOI: 10.21926/obm.geriatr.2302231
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Blame-Like and Forgiveness-Like Judgments between Young People, Healthy Older People, and Older People with Dementia

Abstract: The objective of the present experimental study was to compare how young people, healthy older people, and older people with dementia cognitively integrated<em> </em>three factors (Intention, Consequence, and Apology) when making blame-like judgments (prosecution and revenge) and forgiveness-like judgments (resentment and reconciliation). Thirty-four young people (<em>Mage </em>= 22.12, <em>SD </em>= 3.44), 22 healthy older people (<em>Mage </em>= 71.82, <em&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The objective of our study was to assess the change over time (every 3 months) in cognitive processes in information integration, i.e., how Intention, Consequence, and Apology factors were combined in moral judgments of blame and forgiveness. Our first hypothesis was that the older people with dementia would give greater importance to the Intention factor in both types of moral judgment at time T0 [12,13]. The results confirmed that Intention appeared to be an invariant factor [12,13].…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…The objective of our study was to assess the change over time (every 3 months) in cognitive processes in information integration, i.e., how Intention, Consequence, and Apology factors were combined in moral judgments of blame and forgiveness. Our first hypothesis was that the older people with dementia would give greater importance to the Intention factor in both types of moral judgment at time T0 [12,13]. The results confirmed that Intention appeared to be an invariant factor [12,13].…”
Section: Discussionsupporting
confidence: 57%
“…Our first hypothesis was that the older people with dementia would give greater importance to the Intention factor in both types of moral judgment at time T0 [12,13]. The results confirmed that Intention appeared to be an invariant factor [12,13]. Considering Intention alone may be due to the cognitive impairment associated with dementia [3].…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations